2013
DOI: 10.3233/jad-2012-121543
|View full text |Cite
|
Sign up to set email alerts
|

Episodic-Like Memory for What-Where-Which Occasion is Selectively Impaired in the 3xTgAD Mouse Model of Alzheimer's Disease

Abstract: Episodic memory loss is a defining feature of early-stage Alzheimer's disease (AD). A test of episodic-like memory for the rat, the What-Where-Which occasion task (WWWhich), requires the association of object, location, and contextual information to form an integrated memory for an event. The WWWhich task cannot be solved by use of non-episodic information such as object familiarity and is dependent on hippocampal integrity. Thus, it provides an ideal tool with which to test capacity for episodic-like memory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 42 publications
9
61
1
Order By: Relevance
“…Here, we provide solid evidence for an early impairment in episodic memory in 4-month old Tg2576 mice, correlating with early aggregation of Ab into oligomers, but before plaque formation (Hsiao et al, 1996;Mustafiz et al, 2011). To our knowledge, this is the first report of perturbation in this type of memory in the early phase of AD in AD mice, as few other studies tested this mnemonic deficit at more advanced stages of the pathology (Baglietto-Vargas et al, 2013;Davis et al, 2013;Good et al, 2007). In light of the impaired HPA axis feedback and the key role played by CORT in facilitating the consolidation of emotionally-charged memories (McGaugh and Roozendaal, 2002), it was crucial to monitor episodic memories in minimized stress conditions as presented here.…”
Section: Discussionmentioning
confidence: 74%
“…Here, we provide solid evidence for an early impairment in episodic memory in 4-month old Tg2576 mice, correlating with early aggregation of Ab into oligomers, but before plaque formation (Hsiao et al, 1996;Mustafiz et al, 2011). To our knowledge, this is the first report of perturbation in this type of memory in the early phase of AD in AD mice, as few other studies tested this mnemonic deficit at more advanced stages of the pathology (Baglietto-Vargas et al, 2013;Davis et al, 2013;Good et al, 2007). In light of the impaired HPA axis feedback and the key role played by CORT in facilitating the consolidation of emotionally-charged memories (McGaugh and Roozendaal, 2002), it was crucial to monitor episodic memories in minimized stress conditions as presented here.…”
Section: Discussionmentioning
confidence: 74%
“…However a recent series of studies by Davis and colleagues [68,69] evaluated performance of a triple-transgenic model of AD, which has tau pathology as well as APP and PS1 mutations, on several variants of the SOR task. They found that younger mice performed normally on SOR, RR and OIP tasks, but showed a relatively selective impairment in a 'what-where-which' task, in which the mice were preexposed to the same pair of objects in the transposed positions in two distinctive contexts ( Figure 5), before being tested with two replicas of one of the objects in one of the contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Also story based tests such as the Logical Memory Story A from the Wechsler Memory scale are often used (Weschler, 1987). In rodents the recently described “What-Where-Which” task (WWWhich task), is an episodic-like task, in which animals are tested for the ability to associate an object (what), with its location (where) and its visuospatial context (which occasion) (Davis et al, 2013a, Davis et al, 2013b). Here the context is being used to distinguish a distinct experience or event.…”
Section: Behavioral Studies In Rodentsmentioning
confidence: 99%
“…It has been shown through lesion studies that the ability to successfully associate these three factors, what, where, which occasion, is dependent on an intact hippocampus (Eacott and Norman, 2004, Langston et al, 2010, Langston and Wood, 2010). Also using this task an age dependent decline can be observed in the 3xTg-AD mouse model (Davis et al, 2013a, Davis et al, 2013b). An alternate version of this task distinguishes the episodic event using a time component in place of the visuospatial context, the What-where-when task (WWWhen task), however it is thought that this version of the task does not truly probe episodic memory.…”
Section: Behavioral Studies In Rodentsmentioning
confidence: 99%